Liquidity, Capital Structure, and Asset Utilisation as Determinants of Profitability: Evidence from Food and Beverage Sub-Sector Firms Listed on the Indonesia Stock Exchange (2021–2024) - Syarifah Fadhila Meutya; Hadi Suriono (Privietlab, 2026)
This study examines the partial and joint association between three fundamental financial ratios — liquidity (Current Ratio, CR), capital structure (Debt-to-Equity Ratio, DER), and asset utilisation (Total Assets Turnover, TATO) — and profitability (Return on Assets, ROA) in food and beverage (F&B) sub-sector firms listed on the Indonesia Stock Exchange (IDX) over the post-pandemic period of 2021–2024. The study draws on trade-off theory, pecking-order theory, and the resource-based view of asset productivity. A purposive sampling procedure produced an initially balanced short panel of 17 firms over four fiscal years (n = 68 firm-year observations) after exclusion of firms that did not satisfy the continuous-listing criterion throughout 2021–2024. To address heavy-tailed financial-ratio distributions, the baseline pooled multiple regression is supplemented by a sensitivity analysis on a residual-trimmed subset (n = 32) and by firm fixed-effects estimation. Diagnostic tests (Kolmogorov-Smirnov for normality, VIF for multicollinearity, Glejser test for heteroscedasticity, Durbin-Watson for autocorrelation) are reported transparently. Results on the trimmed analytical sample indicate that, partially, CR is not significantly associated with ROA (β = 0.224, t = 1.37, p = 0.182), DER is positively and significantly associated with ROA (β = 0.759, t = 5.29, p < 0.001), and TATO is not significantly associated with ROA (β = −0.108, t = −0.69, p = 0.497). Jointly, the three predictors significantly explain ROA variation (F(3, 28) = 9.51, p < 0.001; Adj. R² = 0.452). The Durbin-Watson statistic (DW = 0.751) indicates positive first-order autocorrelation, which the study acknowledges as a substantive limitation, and the substantial reduction in sample size during outlier handling is reported transparently. Results are interpreted as associational rather than causal, and the positive DER–ROA coefficient is interpreted as consistent with a trade-off interpretation in the studied sample rather than as evidence of an optimal-leverage threshold. The study contributes to the corporate-finance literature on emerging-market F&B profitability and offers implications for managers, investors, and capital-market regulators.